Mechanical and antimicrobial property of different surface treated glass ionomer cements under desiccated condition - Hemalatha Hiremath; Chhaya Harinkhere; Pooja Misar; Kshitij Sabley; Trupti Bajpai (Wolters Kluwer Medknow Publications, 2021)
Background: The purpose of this in vitro study was to evaluate the effect of five different surface treatments on the mechanical property and antimicrobial effect of three desiccated glass ionomer cements. Materials and Methods: In this in vitro experimental study, 300 rectangular blocks of three different restorative materials were fabricated using an aluminum mold, Group I (n = 100) Micron bioactive, Group II (n = 100) GC Fuji IX GP Extra, and Group III (n = 100) bioglass R. These blocks were stored in 100% humidity for 24 h and then placed in air to desiccate for another 24 h. These groups were further divided into two major groups (n = 50) for both mechanical (Flexural) and antimicrobial testing. The blocks of mechanical and antimicrobial groups were further divided into five subgroups (n = 10) based on the medias used for surface treatment (senquelNaF, MI varnish, chlorhex plus, kedodent mouthwash, and 100% humidity [control]). Flexural strength (FS) was measured using the universal testing machine. Fracture strength of groups was compared using the one-way analysis of variance and Tukey's post hoc test with P ≤ 0.05 considered statistically significant. Antimicrobial effect was carried out by covering the specimens in a suspension of Streptococcus mutans followed by incubation for 24 h. The blocks were later washed, vortex mixed, serially diluted, and plated. Ccolony-forming unit/ml was calculated after 3 days of incubation. Data were then analyzed using the Kruskal-Wallis and Mann-Whitney U nonparametric test, with P ≤ 0.05 considered statistically significant. Results: Micron bioactive with the surface treatment of MI varnish significantly exhibited highest FS. Surface treatment of desiccated restorative materials with chlorhex plus exhibited no growth of S. mutans. GC Fuji IX GP Extra with surface treatment of MI varnish exhibited highest reduction in S. mutans growth compared to other experimental group. Conclusion: Surface treatment of restorative material with MI varnish improved their mechanical and antimicrobial property while among three restorative materials Micron bioactive showed better mechanical property, whereas GC Fuji IX GP Extra exhibited better antimicrobial property.